TENSILE STRENGTH ANALYSIS OF SEA PANDAN LEAVES (PANDANUS TECTORIUS) FIBER REINFORCED EPOXY COMPOSITE - Hartini, Dwi; Pinandita, Lazuardy Rahendra; Mubarak, Pramuda Naufal (Institut Teknologi Dirgantara Adisutjipto, 2022)
The use of sea pandan leaves (pandanus tectorius) as a composite material is intended to reduce the use of synthetic fibers and increase the use of sea pandan leaves which are still wasted. This study aims to determine the tensile strength of the fiber composite of sea pandan leaves based on the manufacturing method and the direction of the fiber used. Composite manufacture using Hand Lay Up and Vacuum Bag methods. The direction of the fiber used is 00 and 900. Tensile test is based on ASTM D3039. The results showed that the composites made using the Vacuum Bag method had a higher tensile strength than the composites made using the Hand Lay Up method, which was 16.54 MPa for the 00 fiber direction and 13.60 MPa for the 900 fiber direction. The tensile strength of the composite using the 00 fiber direction is higher than the composite using the 900 fiber direction, which is 6.48 MPa for the Hand Lay Up method and 16.54 MPa for the Vacuum Bag method.